Detrimental Effect of Chronic Hypertension on Leptomeningeal Collateral Flow in Acute Ischemic Stroke. Issue 7 (July 2019) - Fujita, Kyohei; Tanaka, Kanta; Yamagami, Hiroshi; Ide, Toshihiro; Ishiyama, Hiroyuki; Sonoda, Kazutaka; Satow, Tetsu; Takahashi, Jun C.; Ihara, Masafumi; Koga, Masatoshi; Yokota, Takanori; Toyoda, Kazunori
Abstract : Background and Purpose—: We aimed to evaluate the effect of chronic hypertension on acute leptomeningeal collateral flow in patients with large-vessel ischemic stroke using digital subtraction angiography, which is the gold standard for the assessment of collateral circulation. Methods—: Of the consecutive ischemic stroke patients from October 2011 to December 2017 seen in our institution, patients with acute occlusion of the M1 segment of the middle cerebral artery confirmed on initial digital subtraction angiography were enrolled. Chronic hypertension was defined as its documentation before the index stroke or as the administration of antihypertensive medications before onset. Angiographic leptomeningeal collateral flow was evaluated according to the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology Collateral Flow Grading System and dichotomized the findings into excellent (grade 3–4) or poor (grade 0–2) collateral status for analysis. Results—: Of the 3759 consecutive ischemic stroke patients, 100 patients were analyzed. Thirty-nine patients (39%) had poor collateral status. Patients with poor collateral status were older, more frequently male, and had chronic hypertension more frequently, shorter time from onset to angiography, and higher admission systolic blood pressure than those with excellent collateral status. Multivariable logistic analysis with prespecified covariates showed a significantly positive association between chronic hypertension and poor collateral status (odds ratio, 2.80; 95% CI, 1.08–7.70; P =0.034). This association was independent of admission systolic blood pressure. The proportion of patients with poor collateral status increased in a stepwise manner in patients without chronic hypertension, hypertensive patients with premorbid antihypertensive medications, and hypertensive patients without antihypertensive medications ( P for trend <0.001). Conclusions—: Our data suggest that chronic hypertension has a detrimental effect on acute leptomeningeal collateral flow in patients with cerebral large-vessel occlusion. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02251665.